Locations of Eastern Baltic Sieges and Battle Sites in Written Sources of the Livonian Order - Brazdžiūnas, Mantas (Vilnius University Open Series, 2025)
This paper analyses possible locations of sieges and battles. The analyses were made mainly by using the Livonian chronicle and the Livonian Rhymed chronicle as well as supplementary literature. The basic information on sieges and battles from written sources has been compiled into three separate tables: a general table for sieges and battles, and separate tables for sieges and battles. The analysed potential locations for sieges and battles are marked on two separate maps. The first map shows the locations of the sieges and the dates when the siege took place. The colour of the dates symbolises the army that was besieging a place/structure. The second map shows the approximate locations of the battles and the dates when the battle took place. The colours of the dates symbolise the army that won the battle.
Keywords: Livonian Chronicle; Livonian Rhymed Chronicle; Eastern Baltic; Estonia; Latvia; Lithuania; Russia; Siege site; Battle site